The short-chain fatty acid butyrate exerts a specific effect on VE-cadherin phosphorylation and alters the integrity of aortic endothelial cells - Guo, Jiangang; Terhorst, Inka; Stammer, Paul; Ibrahim, Abdulhakim; Oberhuber, Alexander; Eierhoff, Thorsten (Frontiers in Cell and Developmental Biology, 2023)
Short-chain fatty acids (SCFA) like butyrate (BUT) largely influence vascular integrity and are closely associated to the onset and progression of cardiovascular diseases. However, their impact on vascular endothelial cadherin (VEC), a major vascular adhesion and signaling molecule is largely unknown. Here we explored the effect of the SCFA BUT on the phosphorylation of specific tyrosine residues of VEC (Y731, Y685 and Y658), which are reported to be critical for VEC regulation and vascular integrity. Moreover, we shed light on the signaling pathway engaged by BUT to affect phosphorylation of VEC. Thereby, we used phospho-specific antibodies to evaluate phosphorylation of VEC in response to the SCFA sodium butyrate (BUT) in human aortic endothelial cells (HAOEC) and performed dextran assays to analyze permeability of EC monolayer. The role of c-Src and SCFA receptors FFAR2 and FFAR3 for induction of VEC phosphorylation was analyzed using inhibitors and antagonists for c-Src family kinases and FFAR2/3 respectively, as well as by RNAi-mediated knock down. Localization of VEC in response to BUT was assessed by fluorescence microscopy. BUT treatment of HAOEC resulted in specific phosphorylation of Y731 at VEC with minor effects on Y685 and Y658. Thereby BUT engages FFAR3 and FFAR2 as well as c-Src kinase to induce phosphorylation of VEC. VEC phosphorylation correlated with enhanced endothelial permeability and c-Src-dependent remodeling of junctional VEC. Our data suggest that BUT, a SCFA and gut microbiota derived metabolite impact vascular integrity by targeting VEC phosphorylation with potential impact for pathophysiology and therapy of vascular diseases.